On the asymptotic expansion of the remainder term in the case of convergence to the Poisson law - Grigelionis, B. (Lithuanian Mathematical Journal, 1962)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: Б. Григелионис, Об асимптотическом разложении остаточного члена в случае сходимости к закону Пуассона B. Grigelionis. Apie liekamojo nario asimptotinj išdėstymą konvergencijos į Puasono dėsnį atveju